Analisis Pengaruh Lingkungan Kerja dan Gaya Kepemimpinan terhadap Turnover Intention Karyawan pada PT. Payung Mitrajaya Mandiri Bangka Belitung - Jehan Erwita Sari; Prihatin Lumbanraja; Nismah Panjaitan (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of work environment and leadership style on employee turnover intention at PT. Payung Mitrajaya Mandiri Bangka Belitung, both partially and simultaneously. The high level of turnover intention observed within the company has become a critical concern, given its substantial implications for organizational operational continuity and productivity. This research employed a quantitative approach with an associative research design. The population and sample of the study consisted of all 86 permanent employees of PT. Payung Mitrajaya Mandiri, selected through total sampling technique. Data were collected using a structured questionnaire with a 5-point Likert scale that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression, F-test (simultaneous), t-test (partial), and coefficient of determination through SPSS software. The results of this study reveal that: (1) work environment has a positive and significant effect on employee turnover intention (β = 0.566; t = 5.453; p = 0.000 < 0.05), with a beta value of 0.665, making it the most dominant variable; (2) leadership style has a positive and significant effect on employee turnover intention (β = 0.257; t = 2.471; p = 0.016 < 0.05); and (3) simultaneously, work environment and leadership style have a significant combined effect on employee turnover intention (F = 62.950; p = 0.000 < 0.05). These findings indicate that an unconducive work environment and an ineffective leadership style—as perceived by the majority of employees—are the primary contributing factors to the elevated turnover intention within the organization. This study concludes that improving work environment conditions and enhancing leadership quality represent the most urgent strategic interventions for PT. Payung Mitrajaya Mandiri in its efforts to reduce actual turnover rates. Management is advised to conduct a comprehensive workplace audit, develop leadership training programs based on 360-degree feedback mechanisms, and implement a periodic turnover intention monitoring system as part of an integrated employee retention strategy.   Keywords: Turnover Intention, Work Environment, Leadership Style, Employee Retention, PT. Payung Mitrajaya Mandiri